Who gets jobs matters: Monetary policy and the labour market in HANK and SAM - Uroš Herman; Matija Lozej (European Central Bank (ECB), 2023)
This paper first provides empirical evidence that labour market outcomes for the less educated, who also tend to be poorer, are substantially more volatile than labour market outcomes for the well-educated, who tend to be richer. We estimate job finding rates and separation rates by educational attainment for several European countries and find that job finding rates are smaller and separation rates larger at lower educational attainment levels. At cyclical frequencies, fluctuations of the job finding rate explain up to 80% of the unemployment fluctuations for the less educated. We then construct a stylised HANK model augmented with search and matching and ex-ante heterogeneity in terms of educational attainment. We show that monetary policy has stronger effects when the job market for the less educated and hence poorer is more volatile. The reason is that these workers have the most procyclical income coupled with the highest marginal propensity to consume. An expansionary monetary policy shock that increases labour demand disproportionally affects the labour market segment for the less educated, causing a strong increase in their consumption. This further amplifies labour demand and increases labour income of the poor even more, amplifying the initial effect. The same mechanism carries over to forward guidance.
Keywords: E40; E52; J64; 330; Heterogeneous agents; Search and matching; Monetary policy; Business cycles; Employment